Investigating Effective Factors on Export Performance with Emphasis on the Role of Export Sector Capabilities: A Study in Pegah Zanjan Company - Farrokhi; Hossein Mohammadi, Elham (British Journal of Marketing Studies, 2017)
Export plays an important role in the economic development of countries, at the enterprise level; exports create growth opportunities for companies. By expanding the level of access to foreign markets, the company can reach a higher level of production. The underlying factors that encourage countries and companies for international trading are complex and many .Theorization in the field of international trade has tried to explain the patterns of trade between countries by identifying these factors. This research is descriptive and survey oriented in method and also is a kind of applied research in purpose. In this research, a standard questionnaire is used to collect data that is completed through face-to-face interviews. The statistical population of this research is 202 personnel of Pegah Zanjan Company. The Morgan table was used to estimate the sample size of 127 people. Data were collected using a questionnaire and simple random sampling. In this study, the Cronbach’s alpha, which was 0.76, was used for evaluation. Also descriptive and inferential statistics were used to analyze the data. All statistical analyzes were performed using SPSS software. The results show that the independent variables of this research have the ability to predict about 66% of the dependent variable. The results of the research show that Human Resources Strategic Management variables and competition intensity have a significant effect on the capabilities of the export sector.